PH-responsive, antibacterial and antioxidant bio-based composite membrane and preparation method thereof
The bio-based composite membrane with a three-layer structure design solves the problem of color passivation caused by the blending of styraxin and cinnamic acid, achieves antibacterial effect against Gram-positive and Gram-negative bacteria, improves the color sensitivity and antioxidant capacity of the pH indicator membrane, and has good mechanical properties and reversibility.
Patent Information
- Application Number
- CN202511616343.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-06
- Publication Date
- 2026-01-27
AI Technical Summary
Existing bio-based pH indicator membranes have insufficient antibacterial effect against Gram-negative bacteria, and the co-mixing of cinnamic acid and styraxin leads to the deactivation of the colorimetric response, making it difficult to achieve efficient pH indication and broad-spectrum antibacterial integration.
A three-layer structure design is adopted, with styracin and cinnamic acid placed on both sides of the composite membrane, and the middle layer is a bacterial cellulose/polyvinyl alcohol layer to isolate the two from contact, which are respectively layer I and layer III. Layer I provides pH response indication, and layer III provides antibacterial activity. The concentration of styracin and cinnamic acid and the amount of polyvinyl alcohol added in each layer are optimized to avoid mutual interference.
It achieves significant antibacterial effects against both Gram-positive and Gram-negative bacteria, improves colorimetric sensitivity, enhances antioxidant capacity, exhibits good mechanical properties, and has reversible color changes, making it suitable for dynamic monitoring of food freshness.
Smart Images

Figure CN121403787A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to food packaging materials and functional film technology, and more particularly to a bio-based composite preservation film capable of pH indication and broad-spectrum antibacterial function, and its preparation method. Background Technology
[0002] With increasing awareness of food safety and the development of green and intelligent sensing packaging, traditional food preservation films, mainly composed of petroleum-based polymers such as polyethylene (PE), are limited due to their difficulty in degradation and high environmental burden. While bio-based and biodegradable materials offer environmental advantages, they are constrained by cost, film formation, and overall performance. Bacterial cellulose, possessing high purity, high crystallinity, and a three-dimensional nanonetwork, can be compounded with polyvinyl alcohol to improve density and toughness, making it suitable as a substrate for food contact and intelligent packaging. The natural pigment squalene is highly sensitive to pH, enabling visible color changes under acidic and alkaline conditions. However, single pH indicator films have limited antibacterial ability, especially against spoilage microorganisms such as Gram-negative bacteria. To achieve "indication + antibacterial," cinnamic acid, with broad-spectrum antibacterial activity, is often introduced; however, co-blending it with squalene can lead to dye aggregation due to the weakly acidic buffering effect of cinnamic acid and possible π-π stacking and hydrogen bonding with squalene, resulting in a narrowed color development range, an increased color change threshold, and a desensitized pH response. There is an urgent need for a composite design that combines structure and formulation to physically isolate the two types of active components from direct contact, while taking into account indication sensitivity, broad-spectrum antibacterial effect, and membrane mechanical / processing properties. Summary of the Invention
[0003] Given that the original squalene-loaded film is effective against Gram-positive bacteria but has limited effect against Gram-negative bacteria, this invention introduces cinnamic acid as a broad-spectrum antibacterial agent into the composite preservation film. However, directly mixing cinnamic acid and squalene to form a film results in the passivation of the colorimetric response of squalene. To solve this problem, this invention proposes a three-layer structure design that physically isolates cinnamic acid and squalene from direct contact: two functional films are placed on both sides of the three-layer structure, with the middle bacterial cellulose / polyvinyl alcohol layer serving as an isolation layer, thus achieving both indication and antibacterial functions.
[0004] The objective of this invention is achieved through the following technical solution: A pH-responsive bio-based composite membrane with antibacterial and antioxidant properties, the composite membrane comprising layer I: styraxin-bacterial cellulose / polyvinyl alcohol layer, layer II: bacterial cellulose / polyvinyl alcohol layer and layer III: cinnamic acid-bacterial cellulose / polyvinyl alcohol layer; The final concentration of styraxin in layer I is 0.01-0.04 mmol / L, the final concentration of cinnamic acid in layer III is 40-100 mmol / L, and the amount of polyvinyl alcohol added in each layer is 30-50% w / w of the dry weight of bacterial cellulose.
[0005] Preferably, the final concentration of styracin in layer I is 0.03 mmol / L, the final concentration of cinnamic acid in layer III is 80 mmol / L, and the amount of polyvinyl alcohol added in each layer is 40% w / w of the dry weight of bacterial cellulose.
[0006] Preferably, the composite film is formed by sequentially stacking a sclerotinol-bacterial cellulose / polyvinyl alcohol layer (layer I) on the surface, a bacterial cellulose / polyvinyl alcohol layer (layer II) in the middle, and a cinnamic acid-bacterial cellulose / polyvinyl alcohol layer (layer III) near the packaged item. Layer I provides pH response indication, while layer III provides antibacterial activity and avoids pH response passivation by isolating styraxin and cinnamic acid from layer II, thus preventing their interaction. This composite membrane exhibits significant color changes in the pH range of 2-12 and has antibacterial activity against Staphylococcus aureus and Escherichia coli, significant DPPH / ABTS free radical scavenging performance, and good mechanical properties.
[0007] The composite membrane exhibits at least a reversible response of 5 cycles in an acid-base cycle test with volatile ammonia / hydrochloric acid while still maintaining a detectable color change.
[0008] The composite membrane is prepared by pretreatment, homogenization, washing, and concentration of bacterial cellulose wet film into a homogenate, as well as extraction and incorporation of styraxin and cinnamic acid, blending with polyvinyl alcohol, and layer-by-layer casting and drying.
[0009] The method for preparing a pH-responsive bio-based composite membrane with both antibacterial and antioxidant properties includes the following steps: S1. The wet bacterial cellulose membrane obtained by fermentation culture of bacterial cellulose-producing bacteria is purified, homogenized and then centrifuged and washed to obtain a bacterial cellulose homogenate. S2. Ferment the strain that produces styraxone to obtain a fermentation broth containing styraxone, extract and freeze-dry to obtain styraxone powder; S3. Preparation of polyvinyl alcohol solution for film formation: Dissolve polyvinyl alcohol to prepare a clear solution with a mass concentration of 30-50 g / L; S4. Functional Layer Formulation and Preparation: Layer I: Take bacterial cellulose homogenate, add 0.01-0.04 mmol / L of styracil and 30-50% w / w of polyvinyl alcohol solution of bacterial cellulose dry weight, and stir to obtain Layer I casting liquid; Layer II: Take bacterial cellulose homogenate and add 30-50% w / w polyvinyl alcohol solution of bacterial cellulose dry weight, stir at 50℃ and about 500 rpm for 1 h to obtain the casting liquid of layer II; Layer III: Take bacterial cellulose homogenate and add cinnamic acid solution with a final concentration of 40-100 mmol / L and 30-50% w / w polyvinyl alcohol solution of bacterial cellulose dry weight, and stir to obtain the casting solution for Layer III; S5. Preparation of composite membrane: Pour the casting solution of layer I in S4 into a plastic petri dish. After drying to form the first membrane layer, pour the casting solution of layer II on top. After drying to obtain a double membrane, pour the casting solution of layer III on top. After drying to form a three-layer composite membrane, remove it and allow it to equilibrate at room temperature to obtain the finished product.
[0010] The bacterial cellulose-producing bacteria include Komagataeibacter europaeus , Komagataeibacter saccharivorans , Acetobacter xylinum , Gluconacetobacter hansenii At least one of ATCC53582.
[0011] The concentration of the bacterial cellulose homogenate is 8-12 g / L, preferably 10 g / L.
[0012] The homogenization conditions are 2000-2800 rpm for 8-12 min; the centrifugation and washing conditions are 6000-10000 rpm for 4-6 min, with 3-5 cycles.
[0013] The strain that produces strychnine is *Serratia marcescens* (Serratia marcescens). Serratia marcescens )GEN-01.
[0014] In step S4, the membrane solutions of layer I, layer II, and layer III are stirred at 300-800 rpm at 40-50°C to obtain a uniform casting solution. Layer I is preferably prepared at 40°C, and layers II / III are preferably prepared at 50°C.
[0015] Application of the bio-based composite membrane in the preparation of food, pharmaceutical and cosmetic packaging materials.
[0016] Preferably, the bacterial cellulose homogenate is prepared using... Gluconacetobacter hansenii The ATCC53582 strain was activated and inoculated into the fermentation medium at an inoculum rate of 5-15%. After static culture for about 5-10 days, a liquid film layer was obtained. The film was then heated and boiled in NaOH solution for about 30 minutes. The purified wet film was coarsely crushed and homogenized at 2000-2800 rpm for 8-12 minutes. After centrifugation, washing, and concentration, a bacterial cellulose homogenate with a concentration of 8-12 g / L (preferably about 10 g / L) was obtained.
[0017] Preparation of styraxin: Picking from a solid plate Serratia marcescensA single colony of GEN-01 was inoculated into a seed culture and cultured for two generations. The culture was then inoculated into a fermentation medium (seed medium and fermentation medium formulation: glucose 20 g / L, peptone 16 g / L, CaCl2 25 g / L, L-proline 7.5 g / L, MgSO4·7H2O 0.2 g / L, FeSO4·7H2O 0.06 g / L) and fermented for 3 days. After extraction with acidic methanol for 6 hours, the culture was centrifuged at 8000 rpm for 10 minutes. The supernatant was collected and pre-frozen at -40°C for 24 hours. Subsequently, the supernatant was dried using a freeze dryer to obtain styraxin powder.
[0018] Functional layer formulation and preparation: I. Indicator layer (Layer I): Take 8-10 g / L bacterial cellulose homogenate and add styracil to make the final concentration 0.01-0.04 mmol / L; then add 30-50% w / w of polyvinyl alcohol by dry weight of bacterial cellulose, and stir at 40℃ and about 500 rpm for 1 h to obtain the indicator layer casting solution; II. Isolation layer (Layer II): Take 8-10 g / L bacterial cellulose homogenate and add 30-50% w / w of polyvinyl alcohol by dry weight of bacterial cellulose. Stir at 50℃ and about 500 rpm for 1 h to obtain the isolation layer casting solution. III. Antibacterial layer (Layer III): Take 8-10 g / L bacterial cellulose homogenate and add cinnamic acid to make the final concentration 40-100 mmol / L; then add 30-50% w / w of polyvinyl alcohol by dry weight of bacterial cellulose, and stir at 50℃ and about 500 rpm for 1 h to obtain the antibacterial layer casting solution. Preferably, when the amount of cinnamic acid is about 80 mmol / L, the antibacterial effect and cost are more balanced; when the amount of polyvinyl alcohol added is about 40% (w / w), the tensile strength and elongation at break are better; the resulting composite film can be cut and sterilized for characterization tests such as antibacterial performance, pH response, antioxidant properties, reversibility of pH response, FT-IR, and thermogravimetric analysis.
[0019] In recent years, biodegradable and intelligent sensing food packaging films based on renewable polysaccharides or proteins have attracted attention. Among them, bacterial cellulose is often used as a green packaging matrix due to its high crystallinity, high specific surface area, and excellent film-forming properties. Polyvinyl alcohol can be compounded with bacterial cellulose to improve toughness and density. The natural pigment squalene is pH sensitive and can undergo visible color changes in acidic and alkaline environments, making it suitable for indicating food freshness. However, experiments have shown that squalene-bacterial cellulose / polyvinyl alcohol indicator films are mainly effective against Gram-positive bacteria (such as Staphylococcus aureus) but have weak inhibition against Gram-negative bacteria (such as Escherichia coli), making it difficult to meet the integrated requirement of "indication + broad-spectrum antibacterial". To improve the inhibition effect against Gram-negative bacteria, the intuitive idea is to introduce cinnamic acid, which has broad-spectrum antibacterial activity, into the same film-forming system. However, in practice, it has been found that when cinnamic acid and squalene are co-layered, the pH color response of squalene is significantly desensitized, resulting in a narrowing of the color change range and an upward shift in the response threshold. Possible reasons include: the weak acidity of cinnamic acid causing a local buffering effect, and the possible π-π stacking and hydrogen bonding between cinnamic acid and cymoxanil, inducing the dye to form H / J aggregates, thereby weakening spectral shift and color saturation. Based on this, the present invention provides a strategy of synergistic structure and formulation, introducing broad-spectrum antibacterial function and avoiding component interference without sacrificing indication sensitivity.
[0020] Compared with the prior art, the present invention has the following beneficial effects: (1) Synergistic function: The three-layer structure physically isolates styraxin and cinnamic acid, avoiding dye aggregation caused by weak acid buffer and intermolecular interaction, and significantly improving pH colorimetric sensitivity and readability;
[0021] (2) Broad-spectrum antibacterial: While maintaining its indicator function, it has significant inhibitory effects on Staphylococcus aureus and Escherichia coli; the overall effect is excellent when the cinnamic acid concentration is about 80 mmol / L.
[0022] (3) Enhanced antioxidant capacity: As the content of styraxin increases, the scavenging rates of DPPH and ABTS free radicals increase, showing good antioxidant capacity;
[0023] (4) Good mechanical and processability: The BC / polyvinyl alcohol compound gives the film high tensile strength and ductility, and the step casting and low temperature drying process is simple and can be scaled up;
[0024] (5) Reversible and visible: The color parameters can be reversibly changed after multiple cycles in acid / alkali volatile environments, making it suitable for dynamic monitoring of food freshness;
[0025] (6) Green and safe: The core raw materials are sourced from friendly sources and are suitable for contact scenarios such as food and medicine, and have the potential for industrial application. Attached Figure Description
[0026] Figure 1 The antibacterial effects of the styraxone-bacterial cellulose / polyvinyl alcohol composite membrane, the cinnamic acid / styraxone-bacterial cellulose / polyvinyl alcohol composite membrane, and the cinnamic acid / styraxone-bacterial cellulose / polyvinyl alcohol three-layer composite membrane in Example 4 are as follows: Figure 2 The diameter of the inhibition zone against Staphylococcus aureus and Escherichia coli in Example 4 is shown in the three-layer composite membrane of cinnamic acid / gibberellin-bacterial cellulose / polyvinyl alcohol with different concentrations of cinnamic acid added. Figure 3 The color development of the three-layer composite membranes of styraxone-bacterial cellulose / polyvinyl alcohol, cinnamic acid / styraxone-bacterial cellulose / polyvinyl alcohol, and cinnamic acid / styraxone-bacterial cellulose / polyvinyl alcohol under different pH conditions is shown in Example 4. Figure 4 The scavenging rate of DPPH and ABTS free radicals on the cinnamic acid / vinylidene-bacterial cellulose / polyvinyl alcohol three-layer composite membrane with different concentrations of vinylidene added in Example 4; Figure 5 The stress-strain curves of the cinnamic acid / gibberellin-bacterial cellulose / polyvinyl alcohol three-layer composite film with different concentrations of polyvinyl alcohol added in Example 4 are shown. Figure 6 The three-layer composite film of cinnamic acid / gibberellin-bacterial cellulose / polyvinyl alcohol in Example 4 is subjected to bending, folding, rolling and gravity tearing. Figure 7 The color index of the cinnamic acid / gibberellin-bacterial cellulose / polyvinyl alcohol three-layer composite film in Example 4 changes under the volatile acid and alkaline environments of ammonia / hydrochloric acid. Figure 8 The Fourier transform infrared (FT-IR) spectrum of the cinnamic acid / gibberellin-bacterial cellulose / polyvinyl alcohol three-layer composite film in Example 4; Figure 9 This is the thermogravimetric analysis (TGA) diagram of the cinnamic acid / gibberellin-bacterial cellulose / polyvinyl alcohol three-layer composite membrane in Example 4; Figure 10 This is the thermogravimetric differential (DTG) diagram of the cinnamic acid / lecithin-bacterial cellulose / polyvinyl alcohol three-layer composite membrane in Example 4. Detailed Implementation
[0027] The present invention will be further described in detail below with reference to examples, but the embodiments of the present invention are not limited thereto. Furthermore, the embodiments described are for illustrative purposes only and should not, and will not, limit the invention as described in detail in the claims.
[0028] The bromide-producing strain in the example is classified as *Serratia marcescens* (…). Serratia marcescensGEN-01 was deposited at the China Center for Type Culture Collection on April 24, 2025, with accession number CCTCC NO: M2025877. This strain is sensitive to pH, and the styracin it produces exhibits significant color changes in response to pH changes, showing reddish-purple under acidic conditions, orange-yellow under neutral conditions, and yellow under alkaline conditions.
[0029] Gluconacetobacter hansenii The ATCC53582 strain was purchased from Beijing Beina Chuanglian Biotechnology Research Institute.
[0030] Example 1
[0031] (1) Obtaining bacterial cellulose homogenate: First, the bacterial cellulose homogenate was prepared by... Gluconacetobacter hansenii ATCC53582 strain was inoculated onto solid plates and cultured at 30℃ for 2 days to activate the strain. A single colony was inoculated into 5 ml of seed culture medium and cultured at 30℃ and 180 rpm for 48 h to obtain the first generation seed culture. The culture broth from the first generation seed culture was inoculated at a 10% inoculation rate into a new seed culture medium and cultured at 30℃ and 180 rpm for 24 h to obtain the seed culture for fermentation. 10% of the seed culture was inoculated into an Erlenmeyer flask containing 50 ml of fermentation medium and fermented at 30℃ for 9 days to obtain bacterial cellulose. The generated bacterial cellulose membrane was removed and repeatedly rinsed with distilled water to remove the culture medium and impurities from the membrane surface. The membrane was then immersed in 0.1 mol / L NaOH solution and boiled at 100℃ for 30 min to remove the bacterial cells and residual culture medium from the liquid membrane, resulting in a milky white, semi-transparent membrane. It was then repeatedly rinsed with distilled water until neutral to obtain purified bacterial cellulose. The purified bacterial cellulose wet membrane was first placed in a grinder and coarsely crushed into small fragments of approximately 1 cm × 1 cm to facilitate subsequent homogenization. These fragments were then suspended in pure water and transferred to a high-speed homogenizer for homogenization at 2400 rpm for 10 minutes to further break down the original wet membrane structure, reduce fiber aggregation, and form a more uniform bacterial cellulose homogenate. After homogenization, the homogenate was washed three times with the addition of an appropriate amount of pure water. Each wash was centrifuged at 8000 rpm for 5 minutes to initially remove supernatant impurities, and the waste liquid was discarded to ensure that residual culture medium, extraneous proteins, or bacterial debris were thoroughly removed. After washing, the washed bacterial cellulose suspension was collected by centrifugation, the supernatant was discarded, and the sediment was retained. The sediment was then redispersed in pure water for concentration until a bacterial cellulose homogenate with a concentration of approximately 10 g / L was obtained.
[0032] Seed culture medium composition: glucose 40 g / L, yeast extract 1 g / L, peptone 7 g / L, disodium hydrogen phosphate dodecahydrate 8 g / L, corn steep liquor powder 6 g / L, ethanol 14 ml / L, acetic acid 1 ml / L, pH=6.0.
[0033] Fermentation medium: glucose 20 g / L, yeast extract 18 g / L, MnSO4 2.58 g / L, MgSO4 4.41 g / L, succinic acid 2.32 g / L, disodium hydrogen phosphate dodecahydrate 8 g / L, ethanol 14 ml / L.
[0034] (2) Obtaining styraxin: Pick up from solid plates Serratia marcescens A single colony of GEN-01 was inoculated into 5 ml of seed culture medium and cultured at 30℃ and 180 rpm for 12 h to obtain the first generation seed culture. The culture broth from the first generation seed culture was inoculated at a 10% inoculation rate into a new seed culture medium and cultured at 30℃ and 180 rpm for 12 h to obtain the seed culture for fermentation. 10% of the seed culture was inoculated into a 100 mL Erlenmeyer flask containing fermentation medium and fermented at 30℃ and 180 rpm for 3 days. After fermentation, the bacterial culture was added to an acidic methanol solution at a volume ratio of 1:99, and then placed in a constant temperature shaking incubator for extraction with light-protected shaking for 6 h. After extraction, the culture was centrifuged at 8000 rpm for 10 min, and the supernatant was collected (if the precipitate still contains pigment, extraction can be repeated until white). The obtained supernatant was pre-frozen at -40℃ for 24 h, and then freeze-dried at -40℃ to obtain styraxin powder.
[0035] Seed culture medium and fermentation medium: glucose 20 g / L, peptone 16 g / L, CaCl2 25 g / L, L-proline 7.5 g / L, MgSO4·7H2O 0.2 g / L, FeSO4·7H2O 0.06 g / L.
[0036] (3) Preparation of polyvinyl alcohol solution: Dissolve polyvinyl alcohol in pure water at 100°C to prepare a 40g / L polyvinyl alcohol solution, and stir thoroughly until completely transparent.
[0037] Example 2
[0038] (1) Layer I: Preparation of styrax-bacterial cellulose / polyvinyl alcohol membrane solution In this embodiment, 5 mL of the bacterial cellulose homogenate (preferably 10 g / L) prepared and purified in Example 1 was first prepared and set aside. Vibrio rubigin was added to the 5 mL bacterial cellulose homogenate to achieve a final concentration of 0.01, 0.02, 0.03, and 0.04 mmol / L, respectively, to obtain a vibrio rubigin / bacterial cellulose solution formulation. Then, 30, 40, or 50% w / w of the dry weight of bacterial cellulose (i.e., 0.375, 0.5, and 0.625 mL of 40 g / L polyvinyl alcohol) was added to the vibrio rubigin / bacterial cellulose solution to obtain a vibrio rubigin-bacterial cellulose / polyvinyl alcohol film formulation solution. The vibrio rubigin-bacterial cellulose / polyvinyl alcohol film solution was continuously stirred at 500 rpm for 1 h in a 40°C water bath to ensure that vibrio rubigin was fully dispersed, combined, and formed a homogeneous mixture in the bacterial cellulose / polyvinyl alcohol mixture.
[0039] (2) Layer II: Preparation of bacterial cellulose / polyvinyl alcohol membrane solution In this embodiment, 5 mL of the bacterial cellulose homogenate (concentration approximately 10 g / L) prepared and purified in Example 1 above was first prepared and set aside. 30, 40, or 50% w / w of polyvinyl alcohol (PVA) based on the dry weight of the bacterial cellulose was added to the above bacterial cellulose solution, i.e., 0.375, 0.5, and 0.625 mL of a 40 g / L PVA solution was added to obtain a bacterial cellulose / PVA film formulation solution. The above bacterial cellulose / PVA film solution was continuously stirred at 500 rpm for 1 h in a 50°C water bath to ensure that the bacterial cellulose / PVA mixture was fully dispersed, combined, and formed a homogeneous mixture.
[0040] (3) Layer III: Preparation of cinnamic acid-bacterial cellulose / polyvinyl alcohol membrane solution In this embodiment, 5 mL of the bacterial cellulose homogenate (concentration approximately 10 g / L) prepared and purified in Example 1 above was first prepared and set aside. Cinnamic acid was added to the 5 mL bacterial cellulose homogenate to achieve a final concentration of 40, 60, 80, or 100 mmol / L in the III-layer system, thus obtaining a cinnamic acid / bacterial cellulose solution formulation. Then, 30, 40, or 50% w / w of polyvinyl alcohol (PVA) based on the dry weight of bacterial cellulose was added to the above cinnamic acid / bacterial cellulose solution, i.e., 0.375, 0.5, and 0.625 mL of a 40 g / L PVA solution was added to obtain a cinnamic acid-bacterial cellulose / PVA film formulation solution. The above cinnamic acid-bacterial cellulose / PVA film solution was continuously stirred at 500 rpm for 1 h in a 50°C water bath to ensure that the cinnamic acid was fully dispersed, combined, and formed a homogeneous mixture in the bacterial cellulose / PVA mixture.
[0041] (4) Preparation of styrax rubigin / cinnamic acid-bacterial cellulose / polyvinyl alcohol membrane solution In this embodiment, 15 mL of the bacterial cellulose homogenate (concentration approximately 10 g / L) prepared and purified in Example 1 above was first taken and set aside. Next, cinnamic acid was added to the 15 mL bacterial cellulose homogenate to achieve a final concentration of 40, 60, 80, or 100 mmol / L in the system. Next, styracil was added to the cinnamic acid-bacterial cellulose solution to achieve a final concentration of styracil in the system of 0.01, 0.02, 0.03, or 0.04 mmol / L. Subsequently, a polyvinyl alcohol solution was prepared: polyvinyl alcohol was dissolved in pure water at 100°C with stirring to prepare a 40 g / L polyvinyl alcohol solution, which was then stirred thoroughly until completely transparent. Then, 30, 40, or 50% w / w of polyvinyl alcohol (polyvinyl alcohol) based on the dry weight of bacterial cellulose was added to the above cinnamic acid / cinnamic acid-bacterial cellulose solution, i.e., 1.125, 1.5, or 1.875 ml of 40 g / L polyvinyl alcohol solution was added to obtain a cinnamic acid / cinnamic acid-bacterial cellulose / polyvinyl alcohol film formulation solution. The above cinnamic acid / cinnamic acid-bacterial cellulose / polyvinyl alcohol film solution was continuously stirred at 500 rpm for 1 h in a 40°C water bath to ensure that cinnamic acid and cinnamic acid were fully dispersed, combined, and formed a homogeneous mixture in the bacterial cellulose / polyvinyl alcohol mixture.
[0042] Example 3
[0043] (1) Preparation of styrax-bacterial cellulose / polyvinyl alcohol composite membrane After stirring the above-mentioned styraxin-bacterial cellulose / polyvinyl alcohol membrane solution from Example 2 (1), the resulting mixed solution was allowed to stand or slightly degassed before being poured into a plastic petri dish. The molded mixture was placed in a 40°C drying oven for 6 hours to evaporate moisture and form a dense, uniform composite film. After drying, the film was removed from the dish and further equilibrated at room temperature for 12 hours to restore a stable state. Finally, a styraxin-bacterial cellulose / polyvinyl alcohol composite membrane was obtained.
[0044] (2) Preparation of cinnamic acid / gibberellin-bacterial cellulose / polyvinyl alcohol composite membrane After stirring the cinnamic acid / sparganin-bacterial cellulose / polyvinyl alcohol membrane solution in Example 2 (4) above, the resulting mixed solution was allowed to stand or slightly degassed before being poured into a plastic petri dish. The molded mixture was placed in a 40°C drying oven for 6 hours to evaporate moisture and form a dense, uniform cinnamic acid / sparganin-bacterial cellulose / polyvinyl alcohol composite membrane. The membrane was removed from the dish and further equilibrated at room temperature for 12 hours to restore a stable state. The final cinnamic acid / sparganin-bacterial cellulose / polyvinyl alcohol composite membrane was obtained.
[0045] (3) Preparation of cinnamic acid / gibberellin-bacterial cellulose / polyvinyl alcohol three-layer composite membrane After stirring the styraxin-bacterial cellulose / polyvinyl alcohol film solution in Example 2 (1) above, the resulting mixed solution was allowed to stand or slightly degassed before being poured into a plastic petri dish. The molded mixture was placed in a 40°C drying oven and dried for 6 hours to evaporate moisture and form a dense and uniform styraxin-bacterial cellulose / polyvinyl alcohol film. After drying, the bacterial cellulose / polyvinyl alcohol film solution stirred evenly in Example 2 (2) above was allowed to stand or slightly degassed before being poured onto the styraxin-bacterial cellulose / polyvinyl alcohol film, and dried in a 40°C drying oven for another 6 hours to obtain a double-layer plastic wrap. Finally, the cinnamic acid-bacterial cellulose / polyvinyl alcohol film solution stirred evenly in Example 2 (3) above was allowed to stand or slightly degassed before being poured onto the double-layer plastic wrap, and dried in a 40°C drying oven for another 6 hours to obtain a cinnamic acid / styraxin-bacterial cellulose / polyvinyl alcohol three-layer composite film. The film was removed from the dish and further equilibrated at room temperature for 12 hours to restore a stable state. The final product was a three-layer composite membrane of cinnamic acid / gibberellin-bacterial cellulose / polyvinyl alcohol.
[0046] Example 4
[0047] (1) Antibacterial properties of composite membranes The antibacterial activity of the composite membrane was determined using the inhibition zone method. Single colonies of *Escherichia coli* (MG1655) and *Staphylococcus aureus* (ATCC 29213) were picked from solid plates and inoculated into 5 ml LB tubes. The culture was obtained by incubation at 37°C and 180 rpm for 12 h. The seed culture was then inoculated at a 5% inoculum volume into 50 ml LB shake flasks and incubated at 37°C and 180 rpm for 12 h. The OD values of the *E. coli* and *Staphylococcus aureus* cultures were measured at 600 nm using a spectrophotometer. 600 Dilute the culture medium to OD using physiological saline. 600 =1, then perform gradient dilution to 10. -3 100 μl of the sample was spread onto an LB agar plate to form a uniform bacterial film. Composite films prepared in Examples 3(1)(2)(3) with a final concentration of 0.03 mmol / L styracil, final concentrations of 40, 60, 80, and 100 mmol / L cinnamic acid, and 40% w / w of polyvinyl alcohol (dry weight of bacterial cellulose) were cut into 1 cm × 1 cm squares or 1 cm diameter circles and then sterilized under UV light for 30 min. The treated film samples were placed in the center of LB agar plates inoculated with *Escherichia coli* and *Staphylococcus aureus*, respectively, and then incubated at 37°C for 12 h. The appearance and diameter of the inhibition zone around the film were recorded. The results are as follows: Figure 1 As shown, A and B correspond to the styraxin-bacterial cellulose / polyvinyl alcohol composite membrane of Example 3 (1). This membrane has significant antibacterial activity against Staphylococcus aureus, but no significant antibacterial activity against Escherichia coli. When cinnamic acid is introduced, the results are as follows. Figure 1 C, D, E, and F correspond to Examples 3(2) and (3), respectively, and exhibit antibacterial activity against *Escherichia coli*. The concentration of cinnamic acid added in Example 3(3) was optimized, with antibacterial zones corresponding to 40, 60, 80, and 100 mmol / L cinnamic acid, respectively. The results are as follows: Figure 2 As shown, the diameter of the inhibition zone first increases and then decreases with the increase of cinnamic acid concentration. Considering cost, a cinnamic acid concentration of 80 mmol / L is selected as the best antibacterial effect.
[0048] (2) pH responsiveness of the composite membrane A series of different pH values (2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12) were prepared using 0.4 mol / L sodium hydroxide solution and 10% (w / v) concentrated hydrochloric acid solution as the base and acid sources, respectively. Composite membranes prepared from the above Examples 3(1), (2), and (3) with a final concentration of 0.03 mmol / L styraxin, a final concentration of 80 mmol / L cinnamic acid, and 40% w / w of polyvinyl alcohol (dry weight of bacterial cellulose) were cut into uniform 1 cm × 1 cm samples. These samples were immersed in pH adjustment solutions ranging from 2 to 12 for approximately 30 seconds, then removed and the surface droplets were shaken off. The images were then photographed at a constant light source at 25°C against a white background using a camera with fixed white balance and a fixed distance. The results are as follows: Figure 3 As shown, in Example 3(1), the erythromycin-bacterial cellulose / polyvinyl alcohol composite membrane is... Figure 3 A in the sample shows a red color under acidic conditions, and the red color gradually shifts to yellow as the pH increases, exhibiting a good pH-responsive color change. However, when cinnamic acid is directly added to the cinnamic acid-bacterial cellulose / polyvinyl alcohol composite membrane, i.e., the results in Example 3 (2) are as follows: Figure 3 As shown in Figure B, the pH responsiveness of the cinnamic acid / pyruvic rubigin-bacterial cellulose / polyvinyl alcohol composite membrane is desensitized with increasing pH, resulting in minimal color change; it only displays a yellow hue under very alkaline conditions. This may be because cinnamic acid itself is a weak acid, acting as a local acid buffer, causing pyruvic rubigin to require a stronger alkali to change color. Alternatively, it may be due to the π-π stacking between cinnamic acid and pyruvic rubigin, coupled with hydrogen bonding, making pyruvic rubigin more prone to forming H / J- aggregates. Once the dye aggregates, the absorption peak shifts / broadens, color saturation decreases, and the pH response is desensitized. To address this issue, a three-layer composite membrane structure was designed to separate cinnamic acid and pyruvic rubigin. The results are as follows... Figure 3 As shown in C, the pH responsiveness of the cinnamic acid / gibberellin-bacterial cellulose / polyvinyl alcohol three-layer composite membrane in Example 3 (3) was significantly improved. When the pH was alkaline, the composite membrane showed a yellow color, and the problem of pH passivation was solved.
[0049] (3) Antioxidant properties of composite membranes Lecithin has good antioxidant properties. The antioxidant properties of the composite membrane can be evaluated by measuring the DPPH and ABTS free radical scavenging rates. A cinnamic acid / lecithin-bacterial cellulose / polyvinyl alcohol three-layer composite membrane with 50 mg of lecithin at final concentrations of 0.01, 0.02, 0.03, and 0.04 mmol / L, cinnamic acid at a final concentration of 80 mmol / L, and polyvinyl alcohol accounting for 40% w / w of the dry weight of bacterial cellulose was placed in 10 ml of pure water and incubated at 30°C and 180 rpm for 12 hours. Then, it was centrifuged at 8000 rpm for 10 min to obtain the supernatant as the extract. A bacterial cellulose homogenate of the same dry weight as in Example 1 (1) was dried in an oven as a control. 2.0 mL of the above extract was mixed with 2 mL of 0.17 mM DPPH ethanol solution and incubated in the dark at room temperature for 30 min. The absorbance of the reaction solution was measured at 517 nm.
[0050]
[0051] Where A1 is the absorbance value of the DPPH solution containing the sample, and A0 is the absorbance value of the DPPH solution.
[0052] A 7.4 mM ABTS solution was prepared and mixed with 5 ml of 2.6 mM potassium persulfate. The mixture was then transferred to a dark place and stored at room temperature for 12 h to form ABTS radicals. The absorbance of the mixture was adjusted to OD at 734 nm by diluting the stock solution with distilled water. 734 =0.7. Mix 1 ml of the above extract with 2 mL of ABTS solution, let stand for 6 min, and then measure the absorbance of the solution at 734 nm.
[0053]
[0054] Where B1 is the absorbance value of the DPPH solution containing the sample, and B0 is the absorbance value of the DPPH solution.
[0055] The results are as follows Figure 4 As shown, with the increase of styraxin concentration, the DPPH free radical scavenging rate and ABTS free radical scavenging rate of the composite membrane gradually increased, reaching a maximum of 57.32% and 88.35%, respectively, indicating that the composite membrane has good antioxidant capacity.
[0056] (4) Mechanical properties of composite membranes The cinnamic acid / vinibromine-bacterial cellulose / polyvinyl alcohol three-layer composite film prepared in Example 3 (3) was equilibrated in a standard environment for at least 48 hours after adding 0.03 mmol / L vinibromine, 80 mmol / L cinnamic acid, and different addition amounts of 30%, 40%, and 50% w / w polyvinyl alcohol. The film was then removed for use. The thickness of the film was measured at three randomly selected locations using vernier calipers. The film was cut into dumbbell-shaped samples with a gauge length of 35 mm and a cross-section of 12 × 2 mm using a cutting device. The samples were then stretched using a stretching machine at a stretching speed of 5.0 mm / min. The results are as follows: Figure 5 As shown, the tensile strength and elongation at break of the three-layer composite film of cinnamic acid / lecithin-bacterial cellulose / polyvinyl alcohol are the highest when the amount of polyvinyl alcohol added is 40% w / w. Therefore, the amount of polyvinyl alcohol added at 40% w / w is the most suitable. Figure 6 The composite membrane is demonstrated to bend, fold, roll up, and tear under gravity.
[0057] (5) Reversibility of pH response of composite membrane The pH-responsive color reversibility of the composite membrane was evaluated using the volatile ammonia method. Briefly, a cinnamic acid / vinibromine-bacterial cellulose / polyvinyl alcohol three-layer composite membrane, prepared in Example 3 (3) with a final concentration of 0.03 mmol / L vinibromine, a final concentration of 80 mmol / L cinnamic acid, and 40% w / w of polyvinyl alcohol (dry weight of bacterial cellulose), was placed 1 cm above the surface of an ammonia solution in a sealed beaker. After the membrane completed its color response, its color parameters were measured using a colorimeter, and it was immediately repositioned 1 cm above the surface of a 0.8 mol / L volatile hydrochloric acid solution in a sealed beaker. After the color response was complete, the color parameters were recorded again. The membrane was then returned to the same position in the ammonia solution to start another cycle. The pH-responsive color reversibility experiment was performed for 5 cycles, with the color index measured after each cycle. The results are as follows: Figure 7 As shown, by simulating the volatile acidic and alkaline gases released during food spoilage, it was found that when the cinnamic acid / lecithin-bacterial cellulose / polyvinyl alcohol three-layer composite film was placed in an ammonia solution, the b value increased, the a value decreased, and the color shifted to yellow. When placed in an acidic volatile solution, the a value increased, the b value decreased, and the color shifted to red. It was found that the film can maintain good sensitivity during 5 acid-base changes, and has the potential to be used as smart food packaging.
[0058] (6) Characterization of composite membranes Using the Thermo Fisher Scientific Nicolet iS20 from the USA at 4000–400 cm -1 Within a range of 4 cm -1Fourier transform infrared (FT-IR) spectra of a cinnamic acid / gynogen-bacterial cellulose / polyvinyl alcohol three-layer composite film were acquired at high resolution.
[0059] The thermal stability of the cinnamic acid / caryophyllin-bacterial cellulose / polyvinyl alcohol three-layer composite film was observed using a thermogravimetric analyzer (Netzsch TGA209F1, Germany) at temperatures ranging from 25°C to 800°C and a heating rate of 10°C / min. The experiment was conducted in an environment with a nitrogen flow rate of 50 mL / min.
[0060] Fourier transform infrared (FT-IR) spectroscopy results are as follows Figure 8 As shown, peaks at 1426, 1105, and 878 cm⁻¹ in the spectrum confirm the cellulose I crystal form and glycosidic bond characteristics; the combination of 2918 / 2857 cm⁻¹ and 1050-1025 cm⁻¹ reflects the blended skeleton of polyvinyl alcohol / bacterial cellulose; peaks at 1636, 1548, and 663-526 cm⁻¹ indicate the presence of the aromatic unsaturated structure of cinnamic acid. Thermogravimetric analysis results are as follows... Figure 9 and Figure 10 As shown, the weight loss of the cinnamic acid / caryophylloxera-bacterial cellulose / polyvinyl alcohol three-layer composite membrane at around 120°C is mainly attributed to the evaporation of physically bound water in the composite membrane. In contrast, the weight loss in the 120-320°C range corresponds to the dehydration of the cellulose backbone and the breaking of glycosidic bonds. The weight loss above 320°C is related to the further cleavage and rearrangement of the carbonized structure, ultimately retaining approximately 20.8% residual carbon at 800°C. This result is consistent with the typical thermal decomposition characteristics of bacterial cellulose, indicating that the sample exhibits a significant main weight loss process in the mid-temperature region and a high residual carbon phase in the high-temperature region, which is beneficial for improving the high-temperature dimensional stability and barrier properties of the composite membrane.
Claims
1. A pH-responsive bio-based composite membrane with antibacterial and antioxidant properties, characterized in that, The composite membrane comprises layer I: a styrax-bacterial cellulose / polyvinyl alcohol layer, layer II: a bacterial cellulose / polyvinyl alcohol layer, and layer III: a cinnamic acid-bacterial cellulose / polyvinyl alcohol layer; The final concentration of styraxin in layer I was 0.01-0.04 mmol / L, the final concentration of cinnamic acid in layer III was 40-100 mmol / L, and the amount of polyvinyl alcohol added in each layer was 30-50% w / w of the dry weight of bacterial cellulose.
2. The pH-responsive bio-based composite membrane with antibacterial and antioxidant properties according to claim 1, characterized in that, The composite membrane exhibits a significant color change within the pH range of 2-12 and possesses antibacterial activity and DPPH / ABTS free radical scavenging properties.
3. The method for preparing a pH-responsive bio-based composite membrane with both antibacterial and antioxidant properties as described in claim 1, characterized in that, Includes the following steps: S1. The wet bacterial cellulose membrane obtained by fermentation culture of bacterial cellulose-producing bacteria is purified and homogenized to obtain a bacterial cellulose homogenate. S2. Ferment the strain that produces styraxone to obtain a fermentation broth containing styraxone, extract and freeze-dry to obtain styraxone powder; S3. Preparation of polyvinyl alcohol solution for film formation: Dissolve polyvinyl alcohol to prepare a clear solution with a mass concentration of 30-50 g / L; S4. Functional layer preparation: Layer I: Add styracil and polyvinyl alcohol solution to bacterial cellulose homogenate and stir to obtain Layer I casting liquid; Layer II: Polyvinyl alcohol solution is added to bacterial cellulose homogenate and stirred to obtain Layer II casting liquid; Layer III: Cinnamic acid and polyvinyl alcohol solution are added to bacterial cellulose homogenate and stirred to obtain Layer III casting liquid; S5. Preparation of composite membrane: Pour the casting liquid of layer I in S4 into the mold, wait for it to dry to form the first membrane layer, then pour the casting liquid of layer II on it, dry to obtain a double membrane, then pour the casting liquid of layer III on it, dry to form a three-layer composite membrane, take it out and equilibrate at room temperature to obtain the finished product.
4. The preparation method according to claim 3, characterized in that, The bacterial cellulose-producing bacteria include Komagataeibacter europaeus , Komagataeibacter saccharivorans , Acetobacter xylinum , Gluconacetobacter hansenii At least one of ATCC53582.
5. The preparation method according to claim 3, characterized in that, The concentration of the bacterial cellulose homogenate was 8-12 g / L.
6. The preparation method according to claim 3, characterized in that, The homogenization conditions were 2000-2800 rpm for 8-12 min.
7. The preparation method according to claim 3, characterized in that, The strain that produces strychnine is *Serratia marcescens* (Serratia marcescens). Serratia marcescens GEN-01, accession number CCTCC NO: M 2025877.
8. The preparation method according to claim 3, characterized in that, In step S4, the solutions of layer I, layer II, and layer III are stirred at 300-800 rpm at 40-50°C to obtain a uniform casting liquid.
9. The preparation method according to claim 8, characterized in that, The first layer membrane solution was stirred at 40°C to obtain a uniform casting solution, and the second and third layer membrane solutions were stirred at 50°C to obtain a uniform casting solution.
10. The application of the bio-based composite film according to claim 1 in the preparation of food, pharmaceutical and cosmetic packaging materials.
